Incidence of Insomnia in Geriatric Patients at the Taliwang Health Center in 2025 - Dijaya, Muhammad Raksa Nagara; Wedayani, Anak Agung Ayu Niti; Pujiarohman, Pujiarohman; Adni, Azizatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Geriatric individuals frequently suffer from insomnia, a sleep problem that significantly affects their general health and wellbeing. The purpose of this study is to examine the association between older adults' age, gender, and likelihood of suffering insomnia. Validated questionnaires were distributed at the Taliwang Health Center's Geriatric Clinic as part of a cross-sectional study. The findings indicate a significant relationship between aging and sleeplessness., with individuals aged ≥ 60 years being 5.342 times more likely to experience sleep disturbance than younger individuals (p = 0.0001). Gender also plays a significant role, with older men being 1.126 times more likely to suffer from insomnia than older women (p = 0.0001).